Dari Saracen Sampai MCA dan Masa Depan Islam Moderat di Indonesia - Muhammad Asrori (Proceedings of Annual Conference for Muslim Scholars, 2018)
Moderate is the original character of Islam, including Islam of Indonesia. Islam of Indonesia has been living harmony in the life of a nation, religious, although in a different perspective, interpretation and point of view. But everything is still reasonable limits and dynamic. Moderate Islam is suddenly threatened after the development of social media and online media that can be accessed easily and cheaply. Especially after the emergence of groups that spread the hoax, hate speech and SARA (ethnicity, religion, race, and inter-group relations) sentiment. The group is developed a new perspective that tends to be radical, scripturalist and rigid. Worse, they use religion as a weapon just for his political interests in the name of da’wâh and jihâd. Here is a big challenge for the existence of moderate Islam in Indonesia